Comparative Analysis of Acral Melanoma in Chinese and Caucasian Patients - Kai Huang; Yu Xu; Emmanuel M. Gabriel; Subhasis Misra; Yong Chen; Sanjay P. Bagaria (Journal of Skin Cancer)
Background. Acral melanoma (AM) is a rare subtype of melanoma, which is one of the least common in Caucasian patients but is a common subtype of melanoma in Chinese patients. It is unclear if prognosis differs between Chinese and Caucasian patients diagnosed with AM. The aim of our study is to investigate patient characteristics and survival differences between Chinese and Caucasian AM patients. Methods. Two large institutional melanoma databases from Fudan University Shanghai Cancer Center (FUSCC) and Mayo Clinic enterprise were retrospectively reviewed from 2009 to 2015. Clinicopathologic and survival data were collected and analyzed between the two groups. The primary outcome was disease-specific survival (DSS) and was calculated using the Kaplan Meier (KM) method. Results. The Chinese group presented with more advanced disease compared with Caucasians: thicker Breslow depth (median 3.0 mm vs. 1.2 mm, p=0.003), more ulcerated disease (66.1% vs. 29%; p<0.001), and advanced stages (stage II/III 84.3% vs. 37.1%; p<0.001). No significant difference was identified in terms of age at diagnosis, location, histologic subtypes, or node positive rate. The 5-year DSS rate was 68.4% and 73% (p=0.56) in Chinese and Caucasians AM patients, respectively. Male gender, Breslow thickness, ulceration, and positive sentinel lymph nodes were independent poor prognostic factors on multivariate analysis. Conclusions. There appears to be no difference in stage-stratified survival between Chinese and Caucasians, supporting the implementation of clinical trials for AM that could include both Chinese and Caucasian patients.